Effect Of Soil Moisture On Trace Elements Concentrations Using Portable X-ray Fluorescence Spectrometer - Sahraoui, H.; Hachicha, M. (University of Eloued جامعة الوادي, 2017)
Portable X-ray fluorescence (PXRF) technology can offer rapid and cost-effective determination of the trace elements concentrations in soils. The aim of this study was to assess the influence of soil moisture content under different condition on PXRF measurement quality. For this purpose, PXRF was used to evaluate the soil elemental concentrations for Ca, Mg, Cd, Cr, Cu, Ni, Zn, P, Fe, Mn and Pb in 60 samples in a perimeter irrigated with treated wastewater (Cebala Borj Touil, North-east Tunisia). Scanning was conducted under four moisture conditions: in-situ, dried soil at 105°C, 40% moisture content soil and saturated soil. All were then compared relatively to dried sample scans. As expected, the relationship between dried vs both in-situ and 40% moisture content elements concentrations were linear. However, PXRF readings from saturated samples were significantly underestimated compared to the measurements on dry samples. Furthermore, soil moisture content caused a significant under-reporting of elemental concentrations compared to the scanning on dry samples. PXRF acted differently for each element following the moisture content of soil. In fact, attenuation coefficient σ of Cr, Fe and Mn were the most affected by saturation of soil samples, whilst Ca, Mg and Ni were more affected for 40% moisture content while Cd, Pb, Zn, Cu and P were affected for in-situ measurements. Correction equations enhanced the error produced by the water influence moisture content and corrected PXRF measurements.
Article in Journal of Fundamental and Applied Sciences Vol 09, N 01
Keywords: PXRF analysis; Soil; moisture content; trace elements.